PENGARUH PERTUMBUHAN EKONOMI, KETERBUKAAN PERDAGANGAN, DAN STABILITAS POLITIK TERHADAP PERKEMBANGAN PASAR SAHAM ASEAN-5 - Zainuri, Zainuri; Oktavani, Zudella Tria; Viphindrartin, Sebastiana (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This study aims to analyze the effect of economic growth, trade openness, and political stability on stock market developments in ASEAN-5, which includes the Philippines, Indonesia, Malaysia, Thailand, and Vietnam during the period 2008-2020. The sampling method used purposive sampling method using the Panel Vector Error Correct Models (PVECM) analysis method. The results showed that the variable of trade openness significantly negatively affects stock market development in the short and long term. Furthermore, the political stability variable significantly positively affects short and long-term stock market development. Meanwhile, the variable economic growth does not affect stock market development. This study also finds evidence of an interrelation causal between economic growth and stock market development. At the same time, the trade openness variables have a one-way causality, while the political stability variables have no causal relationship.